2000
DOI: 10.1038/sj.bjp.0703666
|View full text |Cite
|
Sign up to set email alerts
|

Effects of volatile solvents on recombinant N‐methyl‐D‐aspartate receptors expressed in Xenopus oocytes

Abstract: 1 We have previously shown that toluene dose-dependently inhibits recombinant N-methyl-Daspartate (NMDA) receptors at micromolar concentrations. This inhibition was rapid, almost complete and reversible. The NR1/2B combination was the most sensitive receptor subtype tested with an IC 50 value for toluene of 0.17 mM.2 We now report on the e ects of other commonly abused solvents (benzene, m-xylene, ethylbenzene, propylbenzene, 1,1,1-trichlorethane (TCE) and those of a convulsive solvent, 2,2,2-tri¯uoroethyl eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
80
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 27 publications
14
80
1
Order By: Relevance
“…For example, Cruz et al [13] showed that toluene nearly eliminated NMDA-stimulated but not kainate-induced currents in Xenopus laevis oocytes with low millimolar potency suggesting that NMDA inhibition may be a common mechanism of action for abused inhalants. Toluene also produced dose-dependent and reversible increases in GABA A and glycine receptor functioning in both Xenopus oocytes and rat hippocampal slices [7].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cruz et al [13] showed that toluene nearly eliminated NMDA-stimulated but not kainate-induced currents in Xenopus laevis oocytes with low millimolar potency suggesting that NMDA inhibition may be a common mechanism of action for abused inhalants. Toluene also produced dose-dependent and reversible increases in GABA A and glycine receptor functioning in both Xenopus oocytes and rat hippocampal slices [7].…”
Section: Discussionmentioning
confidence: 99%
“…Typically inactive, mGluRs function as autoreceptors during elevated neuronal activity to attenuate DA, GABA, glutamate, and acetylcholine release (Cartmell and Schoepp, 2000). Given the widespread influence of mGluRs and the list of ion channel and G-protein coupled receptors affected by toluene, further research is necessary to clarify the cellular sequence of events underlying any toluene-induced behavior (Bale et al, 2002;Cruz et al, 1988;Beckstead et al, 2000;Tsuga et al, 1999Tsuga et al, , 2002. Nevertheless, the above observations at the systems level are consistent with the fact that LY379268 similarly reduces the DA-dependent behavioral effects of PCP and to a lesser extent those of amphetamine (Moghaddam and Adams, 1998;Cartmell et al, 1999Cartmell et al, , 2000aClark et al, 2002).…”
Section: Ly379268 Studies and Toluenementioning
confidence: 99%
“…In addition overall membrane integrity was maintained even though these receptors are sensitive to ethanol (27). These findings also suggest that toluene does not act as a competitive inhibitor of glutamate and the inhibitory effects are not due to it being a direct channel blocker (27). The authors suggest that toluene may affect the transmembrane domain of the receptor thus influencing channel state.…”
Section: Ionotropic Receptor Expressionmentioning
confidence: 59%
“…However toluene had little effect on currents induced in other ionotropic glutamate receptors including 2-amino-3-(3-hydroxy-5-methyl-isoxazol-4-yl)propanoic acid (AMPA) GluA1 or GluA1/2 subunits or kainate GluK2 (old nomenclature GluR6 presented in paper) subunits. In addition overall membrane integrity was maintained even though these receptors are sensitive to ethanol (27). These findings also suggest that toluene does not act as a competitive inhibitor of glutamate and the inhibitory effects are not due to it being a direct channel blocker (27).…”
Section: Ionotropic Receptor Expressionmentioning
confidence: 80%
See 1 more Smart Citation